Pengukuran Kinerja Pondok Pesantren Menggunakan Analitycal Hierarchy Process - Oktafiani, Nur Kartika; Wahdati, Arini Rifqiya; Maharani, Faldadinda Farin; Yaqin, M. Ainul (STIKOM Tunas Bangsa Pematangsiantar, 2020)
Performance is a measure of the success of an organization. The success of an organization is illustrated by the achievements produced with the standard objectives of the organization. to find out the success of an organization it is necessary to measure systematically and rationally so that the goals to be achieved are implemented well. Islamic Boarding School with Analitycal Hierarchy Process (AHP) method. The Analytical Hierarchy Process (AHP) can be used to formulate the priorities of various choices by using several criteria (multi criteria). Recommended criteria are obtained from 52 standard Islamic boarding school data. It is expected to be known: 1) daily performance, 2) weekly performance, 3) monthly performance, 4) annual performance. The results of this study can be seen how great the performance of Islamic Boarding School is.